2014
DOI: 10.1088/1748-6041/10/1/015006
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution of copper mineral phases in biological fluids and the controlled release of copper ions from mineralized alginate hydrogels

Abstract: Here we investigate the dissolution behaviour of copper minerals contained within biocompatible alginate hydrogels. Copper has a number of biological effects and has most recently been evaluated as an alternative to expensive and controversial growth factors for applications in tissue engineering.Precise control and sustained release of copper ions are important due to a narrow therapeutic window of this potentially toxic ion, and alginate would appear to be a good material of choice for this purpose. We found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
2
4
0
Order By: Relevance
“…Also, phosphate mineralized samples contained more Zn(II) than carbonate. These results are in accordance with literature data (Bassett et al, 2015), where it was shown that the amount of copper within alginate network can be greatly increased by incorporating copper minerals into alginate hydrogels. So, the total Zn(II) content in biomaterials can be modified by changing formulation (introducing mineral phase) and choosing mineral precursor.…”
Section: Total Zn(ii) Contentsupporting
confidence: 93%
See 1 more Smart Citation
“…Also, phosphate mineralized samples contained more Zn(II) than carbonate. These results are in accordance with literature data (Bassett et al, 2015), where it was shown that the amount of copper within alginate network can be greatly increased by incorporating copper minerals into alginate hydrogels. So, the total Zn(II) content in biomaterials can be modified by changing formulation (introducing mineral phase) and choosing mineral precursor.…”
Section: Total Zn(ii) Contentsupporting
confidence: 93%
“…Functional groups on polymer matrix and pore density actively affect mineralization process, by changing local concentrations of mineral precursors or nucleation sites formation (Asenath-Smith et al, 2012). It was observed that the presence of alginate affects formation (in terms of size and polymorphism) of calcium carbonate and calcium phosphate crystals (Olderøy et al, 2011;Xie et al, 2010) and Cu-minerals (Bassett et al, 2015). The structural properties of alginate such as monomers composition may also influence the properties of the synthesized mineral phase.…”
Section: Xrd Analysismentioning
confidence: 99%
“…16.5 ± 8.6 μM in human serum [45]). However, as we have demonstrated in our previous study [46] these results can be explained by interactions of Cu(II) with biomolecules like amino acids and sera proteins as normal constituents of cell growth medium [47], meaning that relatively high concentrations of FBS (10%) used in the present study had 'buffering' and protective effects on the cellular viability, through binding the excess of Cu(II). Similar findings were reported previously for human chondrocytes tolerating Cu(II) concentrations up to 2.5 mM in cul-ture, while addition of fetal calf serum increased the cell viability [48].…”
Section: Discussionmentioning
confidence: 70%
“…Panel (B) reprinted with permission from ref. ( Bassett et al, 2014 ) (Copyright 2019; Elsevier). Panel (C) and panel (D) reprinted with permission from ref.…”
Section: Application Of Copper-based Biomaterialsmentioning
confidence: 99%
“…This method not only increased the amount of copper supported by alginate saline gel but also controlled the rate and duration of ion release. By altering the formulation of alginate saline gels containing both ionic and mineral copper, the total copper content was changed and the release time of Cu 2+ could be adjusted from 5 to 32 days ( Figure 3B ) ( Bassett et al, 2014 ).…”
Section: Application Of Copper-based Biomaterialsmentioning
confidence: 99%